Gold-Catalyzed 1,2-Acyloxy Migration/Intramolecular [3+2] 1,3-Dipolar Cycloaddtion Cascade Reaction: An Efficient Strategy for Syntheses of Medium-Sized-Ring Ethers and Amines - Zhao, Changgui; Xie, Xingang; Duan, Shuangshuang; Li, Huilin; Fang, Ran; She, Xuegong (Angewandte Chemie International Edition, 2014)
A highly efficient strategy for the formation of medium‐sized‐ring ethers and amines based on a gold‐catalyzed cascade reaction, involving enynyl ester isomerization and intramolecular [3+2] cyclization, has been developed. Various multisubstituted medium‐sized‐ring unsaturated ethers and amines were obtained through this transformation. This method represents one of the relatively few transition metal catalyzed intramolecular cycloaddition reactions for medium‐sized ring synthesis. Happy medium: A highly efficient strategy for the synthesis of the title compounds has been developed. This transformation successfully demonstrates the power of a gold‐catalyzed cycloaddition reaction to prepare various functionalized medium‐sized rings. This method also represents one of the few transition‐metal‐catalyzed intramolecular cycloaddition reactions for the synthesis of medium‐sized rings. Ts=4‐toluenesulfonyl.